Orthogonally protected cyclohexanehexols by a ``one reaction - one product'' approach: efficient access to cyclitols and their analogs - Jagdhane, Rajendra C.; Shashidhar, Mysore S. (European Journal of Organic Chemistry, 2010)
Differentially protected myo-inositol derivatives were prepared from commercially available myo-inositol through regioselective O-alkylation reactions, which give a single product in each step. These derivatives were converted into six isomeric inositol derivatives carrying orthogonal hydroxy protecting groups. For all these reactions, conditions were chosen to prevent the formation of isomeric products, which obviates the need for separation of isomers and provides the required cyclitol derivative in very good yields. The synthetic potential of these derivatives was illustrated by the conversion of some of the orthogonally protected inositol derivatives into other cyclitol derivatives. Isomeric inositols were also prepared by the global deprotection of all the hydroxy groups.
Keywords: Alkylation; cyclitols; Inositol; Protecting groups; Regioselectivity

Orientation of the beta-hydroxyl group controls the diastereoselectivity during the hydride reduction and grignard reaction of inososes - Jagdhane, Rajendra C.; Patil, Madhuri T.; Krishnaswamy, Shobhana; Shashidhar, Mysore S. (Tetrahedron, 2013)
A comparison of the results of the Grignard reaction and the hydride reduction of the carbonyl group of epi- and scyllo-inososes reveals that the extent of diastereoselectivity of these reactions is decided by the orientation of the beta-hydroxyl group (or its derivative). Presence of an axial beta-hydroxyl group generally results in the formation of relatively larger amount of the axial alcohol as a result of the reduction of the carbonyl group. The possible reasons for the observed differences in diastereoselectivity between the reactions of these isomeric epi- and scyllo-inososes have been discussed. The sequence of reactions reported here provides convenient access to C-allcylated inositols, such as iso-laminitol and iso-mytilitol as well as 2-O-methyl epi-inositol, an epimer of the naturally occurring ononitol. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Cyclitol; diastereoselectivity; Grignard; Inositol; Nucleophile; reduction